2009
DOI: 10.1007/s10495-009-0332-z
|View full text |Cite
|
Sign up to set email alerts
|

Furano-sesquiterpene from soft coral, Sinularia kavarittiensis: induces apoptosis via the mitochondrial-mediated caspase-dependent pathway in THP-1, leukemia cell line

Abstract: Bioassay directed fractionation and purification led to the successful isolation of a furano sesquiterpene, Methyl 5-[(1E,5E)-2,6-Dimethyl octa-1,5,7-trienyl] furan-3-carboxylate (MDTFC), a bioactive component from a soft coral, Sinularia kavarittiensis. Its structure was determined by analyzing (1)H, (13)C NMR and FAB-MS. The results show that MDTFC could efficiently and selectively inhibit the proliferation of several human cancer cell lines. Among all the cell lines, THP-1 was found to be most sensitive (IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 39 publications
1
20
0
1
Order By: Relevance
“…4). The results, which are consistent with those coming from previous studies, 35) suggest that 4d induces apoptosis by internucleosomal DNA cleavage, a biochemical event used as a definitive apoptotic marker that signifies the possibility that 4d is a potential drug lead for cancer chemotherapy.…”
Section: Structuressupporting
confidence: 91%
See 1 more Smart Citation
“…4). The results, which are consistent with those coming from previous studies, 35) suggest that 4d induces apoptosis by internucleosomal DNA cleavage, a biochemical event used as a definitive apoptotic marker that signifies the possibility that 4d is a potential drug lead for cancer chemotherapy.…”
Section: Structuressupporting
confidence: 91%
“…35) Initially, HeLa cells were harvested, washed with phosphate-buffered saline (PBS), and then lysed with digestion buffer containing 50 mM Tris-HCl, 0.5% sodium dodecyl sulfate (SDS), 1 µg/mL proteinase k (pH 8.0), and 10 mM EDTA at 37°C overnight. The cells were then treated with RNase A (0.5 µg/mL) for 1 h at 37°C.…”
Section: -mentioning
confidence: 99%
“…Cancer growth is associated with the loss of cell cycle checkpoints that regulate the passage through cell cycle. These check points monitor the integrity of DNA and ensure that the genes are expressed in a co-ordinate manner [24]. Cell cycle analysis showed an "S-phase" population on DDSD treated B16F10 cells, which indicated that the cell death was caused by apoptosis (Figure 4b and c).…”
Section: Discussionmentioning
confidence: 99%
“…Cell cycle analysis and mitochondrial membrane potential were performed as earlier described protocol [24] at the optimal setting of the instrument and proper filters, the samples were recorded as a FCS file and analyzed by FCS express-4 software after the exclusion of the debris and clumps.…”
Section: Flow Cytometric Analysismentioning
confidence: 99%
“…In the current therapeutic approach, inhibition of the mechanism associated with tumor cell migration/invasion is the key to controlling cancer metastasis [17]. Many of the active ingredients isolated from corals have been shown to possess properties that prevent cancer cell proliferation and metastasis [12,[18][19][20][21][22][23]. …”
Section: Discussionmentioning
confidence: 99%